Feeding intolerance during phototherapy in preterm infants. (12th December 2022) - Dani, Carlo; Ciarcià, Martina; Luzzati, Michele; Nardecchia, Silvia; Petrolini, Chiara; Sarli, Walter Maria; Tellini, Marco; Pratesi, Simone
Abstract: Objective: Many very preterm infants are treated with phototherapy (PT) for hyperbilirubinemia and it has been reported that PT can negatively affect gut perfusion. Thus, our aim was to evaluate the occurrence of feeding intolerance in the course of PT in these patients. Methods: We retrospectively studied infants born at 25 +0 –31 +6  weeks from November 2017 to April 2020 who required PT during the first two weeks of life. Patients were used as their own controls recording for each one the occurrence of feeding intolerance after starting PT and the resumption of feeding tolerance after its termination. Results: We studied 125 preterm infants of whom 58 (46%) developed a feeding intolerance which disappeared in 47 (81%) of them at the end of PT. Regression analysis showed a trend toward a not significant decrease of risk of feeding intolerance in infants with higher birth weight and age at the start of the first course of PT. Conclusion: We found that about half of our patients developed a transient feeding intolerance during PT that ceased in the vast majority of them after termination of the therapy. Further studies are necessary to confirm the correlation between PT and feeding intolerance.